Impact of frailty on complications in patients undergoing common urological procedures: a study from the American College of Surgeons National Surgical Quality Improvement database. (17th January 2016) - Suskind, Anne M.; Walter, Louise C.; Jin, Chengshi; Boscardin, John; Sen, Saunak; Cooperberg, Matthew R.; Finlayson, Emily
Abstract : Objectives: To evaluate the association of frailty, a measure of diminished physiological reserve, with both major and minor surgical complications among patients undergoing urological surgery. Materials and Methods: Using data from the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) from 2007 to 2013, we identified all urological cases that appeared > 1000 times in the dataset among patients aged ≥40 years. Frailty was measured using the NSQIP frailty index (FI), a validated measure that includes 11 impairments, such as decreased functional status and impaired sensorium. We created multivariable logistic regression models using the NSQIP FI to assess major and minor complications after surgery. Results: We identified 95 108 urological cases representing 21 urological procedures. The average frequency of complications per individual was 11.7%, with the most common complications being hospital readmission (6.2%), blood transfusion (4.6%) and urinary tract infection (3.1%). Major and minor complications increased with increasing NSQIP FI. Frailty remained strongly associated with complications after adjustment for year, age, race, smoking status and method of anaesthesia (adjusted odds ratio 1.74 [95% confidence interval 1.64, 1.85] for an NSQIP FI ≥0.18). Increasing NSQIP FI was associated with increasing frequency of complications within age groups (by decade) up to age 81 years and across most procedures. Conclusion: Frailty strongly correlates with risk of postoperative complications among patients undergoing urological surgery. This finding is true within most age groups and across most urological procedures.